Black-tailed Mosquito Culiseta melanura (Coquillett) (Insecta: Diptera: Culicidae) - Eva Buckner; Angelique Showman; C. Roxanne Connelly (EDIS)
The black-tailed mosquito is unusual because it overwinters as larvae while most mosquito species overwinter as either adults or eggs. Culiseta melanura is important because of its role in the transmission cycle of eastern equine encephalitis virus and potentially West Nile virus. Because adult female Culiseta melanura primarily take their blood meals from birds, they are responsible for transmitting eastern equine encephalitis virus between birds. This 6-page fact sheet was written by Eva Buckner, Angelique Showman, and C. Roxanne Connelly, and published by the UF Department of Entomology and Nematology, September 2012.